Asphalt-rubber gap-graded mixture design practices: a state-of-the-art research review and future perspective. Issue 3 (4th May 2017) - Venudharan, Veena; Biligiri, Krishna Prapoorna; Sousa, Jorge B.; Way, George B.
Abstract : The use of asphalt-rubber gap-graded (AR-Gap) mix as a pavement material has gained importance due to its environmental benefits and enhanced performance. This paper reviews the current state-of-the-art pertinent to AR-Gap mix design research and practice. The various mix design practices of AR-Gap mixes adopted by various agencies were summarised. Furthermore, the performance characteristics of AR-Gap mixes such as drain-down, moisture susceptibility, permanent deformation, and fatigue cracking were also documented. The field performances of AR-Gap pavements were also reviewed. Due to an increased use of AR-Gap as a pavement material owing to its several benefits, there exists an extensive scope for further research to understand the material better, which will make it a promising sustainable pavement material in future. Furthermore, considering that AR-Gap mix design and construction technologies are yet to be fully implemented worldwide, the present work aims to be an up-to-date reference to provide benefits and issues associated with the AR-Gap mixes. However, based on the various research questions emanating out of the review process, it was adjudged that there is still further scope for advancing the current state-of-the-art pertaining to the AR-Gap mix design, and the contribution of rubber inclusions in assisting the mix's augmented performance.